Nexus Between Energy Poverty and Technological Innovations: A Pathway for Addressing Energy Sustainability - Batool, Kiran; Zhao, Zhen-Yu; Atif, Faraz; Dilanchiev, Azer (Frontiers in Environmental Science, 2022)
Pakistan has experienced energy poverty, as most of the people live in rural areas. Poor people are stereotyped as collecting the firewood and using the unclean energy sources to meet their residential energy needs. As a result, respondents in the provinces with the highest rates of energy poverty set a high priority on this research. Structured interviews were used to conduct the research in rural parts of Punjab and Sindh provinces. Due to the apparent country's large population and rapid industrialization, conventional energy sources cannot meet the country's present energy needs. Results revealed that energy poverty in rural areas had exposed the residents to security problems such as health dangers, fire accidents, time poverty, financial poverty, illiteracy, and other issues at various levels of severity. As a result, alternative energy sources must be explored. This research aims to determine the best renewable energy choice for Pakistan's rural areas. In terms of pricing, life duration, operation, and maintenance costs, the results show that solar energy is the best renewable energy source for Pakistan. The key barriers that continue to promote energy poverty have been identified. Finally, the study suggests policy recommendation for public and private sectors to overcome energy related barriers to alleviate energy poverty in rural areas by utilizing maximum solar energy.